2023
DOI: 10.1097/apo.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis Management Study—A Prospective Randomized Clinical Trial on Postoperative Endophthalmitis Management in India: An Interim Analysis. Endophthalmitis Management Study Report #3

Taraprasad Das,
Akash Belenje,
Suchita Pandey
et al.

Abstract: Purpose: An interim analysis of the Endophthalmitis Management Study to examine the outcome of inflammation score (IS)–based treatment and antibiotic susceptibility. Design: A prospective randomized study. Patients and Methods: IS was measured on a 0–4 scale from presenting signs in 4 cardinal ocular tissues. The eyes with IS <10 received vitreous tap and intravitreal antibiotics, whereas eyes with IS ≥10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Accordingly, in their consequent studies, they reported erratic inflammation which increases with subsequent interventions which were mandatory in recalcitrant cases and indicated that the severity of the infection is directly correlated with higher IS values, underscoring the utility of this scoring system in assessing the progression of the disease and guiding treatment decisions. 8 These insights highlight the critical need for precise diagnostic tools and tailored therapeutic strategies for managing fungal endophthalmitis. Laboratory diagnosis primarily involves direct microscopic examination, culture on Sabouraud Dextrose Agar (SDA) and Potato Dextrose Agar (PDA), even though it does grow on blood agar, chocolate agar, and brain heart infusion broth.…”
Section: ■ Clinical Features and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in their consequent studies, they reported erratic inflammation which increases with subsequent interventions which were mandatory in recalcitrant cases and indicated that the severity of the infection is directly correlated with higher IS values, underscoring the utility of this scoring system in assessing the progression of the disease and guiding treatment decisions. 8 These insights highlight the critical need for precise diagnostic tools and tailored therapeutic strategies for managing fungal endophthalmitis. Laboratory diagnosis primarily involves direct microscopic examination, culture on Sabouraud Dextrose Agar (SDA) and Potato Dextrose Agar (PDA), even though it does grow on blood agar, chocolate agar, and brain heart infusion broth.…”
Section: ■ Clinical Features and Diagnosismentioning
confidence: 99%
“…Other drugs such as caspofungin and posaconazole showed resistant to 50% of the cases. 8 Since the majority of the cases are multidrugresistant, timely rescue of the vision in fungal endophthalmitis becomes increasingly challenging. Additionally, culture negative and recalcitrant cases pose a serious threat to timely diagnosis and intervention, resulting in greater influx of inflammatory cells disrupting the retinal architecture.…”
mentioning
confidence: 99%
“…Notably, these preliminary findings indicate that the inflammation score serves as a valuable prognostic marker for the disease [15]. Indeed, within an as-yet-unpublished report, the authors engaged in this investigation have taken the bold step of suggesting that this specific parameter emerges as a superior instrument for directing clinical decision-making, particularly in the realm of early-stage disease management [16]. Table 1 provides a summary of the clinical trial studies conducted on the management of post-cataract surgery endophthalmitis.…”
Section: Role Of Early Vitrectomy In Postoperative Endophthalmitismentioning
confidence: 99%